The Effectiveness of Outdoor Learning Influences Students’ Naturalistic Intelligence - Hana, Sarce Rien; Susanti; Camerling, Yosua Feliciano; Wijaya, Hengki (Didache: Journal of Christian Education, 2025)
This study aims to find out how the outdoor learning model influences students’ naturalistic intelligence. Researchers took samples from the entire existing population, namely grade IV students of SD Negeri Inpres Sereh Sentani, totaling 52 people. The reason for selecting students as a whole from the existing population is because the total number of students taught is not too large or relatively small. The method used in this study is a quantitative research method with the following data collection techniques: First, Literature Study. Second, field observations. Third, distributing questionnaires. After the data is collected, the data is analyzed and correlated using the Likert scale technique, rating scale by looking for correlations through Pearson Product Moment correlation analysis to get the result that the effect of the Naturalistic Intelligence model with 3 indicators (a lot of aspirations about nature, interested in the topic of flora and fauna and sensitivity to symptoms nature) for fourth grade students of SD Negeri Inpres Sereh Sentani enter and have reached the level of naturalistic intelligence on the indicator that many aspirations about nature exist (87.62%), the indicator of interest in the topic of flora and fauna exists (92.49%) and the indicator of sensitivity to natural symptoms exist (91.67%). So, it can be concluded that the outdoor learning model is positively related to naturalistic intelligence, including a very high correlation.